The Kindness of Strangers: Transformations of Kinship in Precapitalist Class and State Formation - Gailey, Christine Ward (Culture, 1985)
Structural tensions in kinship relations have led only rarely to class stratification. Using the case of Tongan society in precolonial Polynesia, this paper analyzes some of the reasons for the long-term reproduction of kin-based authority, labor and property relations. Pivotal aspects of kinship relations that must change for classes to emerge are examined. Connections are proposed between class and state formation as processes, and the transformation of autonomous kin societies into ethnicities.